Development of a Grp94 inhibitor. - Duerfeldt, A.S.; Peterson, L.B.; Maynard, J.C.; Ng, C.L.; Eletto, D.; Ostrovsky, O.; Shinogle, H.E.; Moore, D.S.; Argon, Y.; Nicchitta, C.V.; Blagg, B.S. (Journal of the American Chemical Society, 2012)
Heat shock protein 90 (Hsp90) represents a promising therapeutic target for the treatment of cancer and other diseases. Unfortunately, results from clinical trials have been disappointing as off-target effects and toxicities have been observed. These detriments may be a consequence of pan-Hsp90 inhibition, as all clinically evaluated Hsp90 inhibitors simultaneously disrupt all four human Hsp90 isoforms. Using a structure-based approach, we designed an inhibitor of Grp94, the ER-resident Hsp90. The effect manifested by compound 2 on several Grp94 and Hsp90?/? (cytosolic isoforms) clients were investigated. Compound 2 prevented intracellular trafficking of the Toll receptor, inhibited the secretion of IGF-II, affected the conformation of Grp94, and suppressed Drosophila larval growth, all Grp94-dependent processes. In contrast, compound 2 had no effect on cell viability or cytosolic Hsp90?/? client proteins at similar concentrations. The design, synthesis, and evaluation of 2 are described herein.